Two Coptic Epitaphs in the Kom Aushim Storage Magazine - Blumell, Lincoln H.; Hussen, Mohamed (Chronique d’Égypte, 2014)
Abstract This article presents editions of two previously unpublished Coptic inscriptions in the Kom Aushim (Karanis) storage magazine. The two inscriptions are epitaphs, date somewhere between the seventh and tenth century, and are written in the Fayumic dialect.